Extended spectrum β‐lactamase‐producing Escherichia coli faecal carriage in Spanish travellers returning from tropical and subtropical countries. (26th March 2014) - Solé, M.; Pitart, C.; Oliveira, I.; Fàbrega, A.; Muñoz, L.; Campo, I.; Salvador, P.; Álvarez‐Martínez, M. J.; Gascón, J.; Marco, F.; Vila, J.; Cantón, R.
Abstract The aim of this study was to investigate the prevalence of extended‐spectrum β‐lactamase (ESBL) ‐producing Escherichia coli in stool samples from 457 patients with travellers' diarrhoea who had travelled to tropical and subtropical countries. Ninety‐seven ESBL‐producing E. coli strains were isolated from 17.9% of the patients (82/457). CTX‐M‐15 was the most prevalent enzyme (80%) and India was the most visited country and showed the highest prevalence of positive samples (37.4%).